2020
DOI: 10.3390/ani10010102
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Testicular Gene Expression in Normal and Cryptorchid Horses

Abstract: Testes produce sperm, and investigations into gene expression in the testes will enhance the understanding of the roles of testicular genes in male reproduction. Cryptorchidism, the failure of one or both testes to descend into the scrotal sac, is a common congenital malformation in horses. The major clinical consequence of this abnormality is impaired fertility. The aim of this study was to analyze the expression patterns of testicular genes and to identify the differentially expressed genes (DEGs) in testes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…22 Cryptorchidism has been attributed to 4 primary mechanisms: failure of the gubernaculum to enlarge the inguinal ring, failure of regression of the gubernaculum, primary testicular abnormalities (cystic rete testis or neoplasia) and persistence of the suspensory ligament of the testis. 1,3,23,24 It has been shown that equine cryptorchid testes have a decreasein immunoreactive INSL-3 in the testicular interstitial cells. 25 Also, serum INSL3 was found to be lower in bilaterally cryptorchid stallions and unilaterally cryptorchid stallions following removal of the scrotal testis compared to intact and unilateral cryptorchid stallions with 1 scrotal testis.…”
Section: Pathophysiology Of Cryptorchidismmentioning
confidence: 99%
“…22 Cryptorchidism has been attributed to 4 primary mechanisms: failure of the gubernaculum to enlarge the inguinal ring, failure of regression of the gubernaculum, primary testicular abnormalities (cystic rete testis or neoplasia) and persistence of the suspensory ligament of the testis. 1,3,23,24 It has been shown that equine cryptorchid testes have a decreasein immunoreactive INSL-3 in the testicular interstitial cells. 25 Also, serum INSL3 was found to be lower in bilaterally cryptorchid stallions and unilaterally cryptorchid stallions following removal of the scrotal testis compared to intact and unilateral cryptorchid stallions with 1 scrotal testis.…”
Section: Pathophysiology Of Cryptorchidismmentioning
confidence: 99%
“…In horses, cryptorchidism is a common congenital malformation associated with the failure to descend by one or both testes into the scrotal sac. The major clinical consequences resulting from elevated temperatures in the undescended testes are impaired fertility and a significantly increased risk of testicular malignancy [29]. It is a well-known fact that cryptorchid testis is incapable of producing spermatozoa, or, in some cases when the retained testis is located in the inguinal canal close to the scrotum, rare production of spermatozoa has been noted [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Three sets of transcriptome data, including donkey testis and epididymis tissues, as well as horse testis tissue, were downloaded and a total of 65.6 Gb of raw data was obtained. Accession numbers were listed as follows: donkey testis, donkey epididymis [PRJNA512590, PRJNA431818] [ 7 , 18 ], horse testis [PRJNA509608, PRJNA395221] ( Supplementary Table S1 ) [ 4 , 19 ].…”
Section: Methodsmentioning
confidence: 99%